Gas Chromatographic Analysis of Medium Chain Fatty Acids in Coconut Oil - Julius Pontoh (The Journal of Pure and Applied Chemistry Research, 2016)
Analysis of medium chain of fatty acids in coconut oil becomes important due to their roles in health issues.  The present analysis methods for fatty acids present in food mainly focused to the overall fatty acid concentration.  The analytical method for specific medium chain fatty acids is not so much be given attention.  This research is focused to the analytical methods for these particular fatty acids in coconut oil.  Several analytical methods were compared including acid catalyzed, basic catalyzed and acid boron trifluoride catalyzed derivatization.  The response of each fatty acid toward the derivatization methods are different.  Formation of the fatty acid methyl ester from caprylic and capric was low for acid catalyzed method compared to basic catalyzed method and acid boron trifluoride catalyzed methods.  This finding shows that the kinetics of the esterification among the fatty acids are not the same.  The analysis of all fatty acids in coconut oil is better using basic catalyzed than the other methods.